2013
DOI: 10.1371/journal.pone.0072049
|View full text |Cite
|
Sign up to set email alerts
|

Inverse Association between Hepatitis B Virus Infection and Fatty Liver Disease: A Large-Scale Study in Populations Seeking for Check-Up

Abstract: BackgroundAlthough many studies have attempted to clarify the association between hepatitis B virus (HBV) infection and fatty liver disease, no prior studies have emphasized the relationship of HBV and fatty liver regarding different demographics of age and body mass index (BMI).AimTo investigate the correlation of HBV and fatty liver in the different demographics of age and BMI.MethodsWe enrolled consecutive subjects who had received health check-up services at the Taipei Veterans General Hospital from 2002 t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
88
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(94 citation statements)
references
References 44 publications
(55 reference statements)
6
88
0
Order By: Relevance
“…However, according to the current reports [7,8,11,17,18,[103][104][105][106][107][108][109][110], the prevalence of NAFLD in CHB ranges widely from 13.6 to 59.3 % ( Table 1). The significant divergence may be due to the differences in ethnicity, demography, and the precise criterion in the studies.…”
Section: Clinical Study Prevalence and Causative Analysis Of Steatosimentioning
confidence: 99%
See 1 more Smart Citation
“…However, according to the current reports [7,8,11,17,18,[103][104][105][106][107][108][109][110], the prevalence of NAFLD in CHB ranges widely from 13.6 to 59.3 % ( Table 1). The significant divergence may be due to the differences in ethnicity, demography, and the precise criterion in the studies.…”
Section: Clinical Study Prevalence and Causative Analysis Of Steatosimentioning
confidence: 99%
“…Such an inverse relationship between CHB and MS is consistent with the result from another large population-based crosssectional study conducted in Taiwan, in which a total of 53,528 subjects were enrolled [111]. If further stratified by age and BMI, according to a large-scale cross-sectional study of 33,439 Taiwan CHB patients, those who were over 50 years old or with body mass index (BMI) over 22.4 kg/m 2 presented a more pronounced negative relationship with fatty liver disease than those who were not [109]. These findings may be attributable to the observation that HBV DNA is positively associated with adiponectin [110]: The decrease in adiponectin, a key regulator of insulin sensitivity secreted by adipose tissue, is confirmed to be a causative factor for IR and the pathogenesis of NAFLD.…”
Section: Clinical Study Prevalence and Causative Analysis Of Steatosimentioning
confidence: 99%
“…Current hepatitis B virus (HBV) infection is a leading aetiological factor of liver cirrhosis and HCC worldwide, especially in Africa and the Western Pacific region . Recently, several observational studies have paid attention to the topic of current HBV infection and fatty liver . However, their findings are rather inconclusive.…”
Section: Introductionmentioning
confidence: 99%
“…In a more recent study by Enomoto et al (17), they found a low frequency histological hepatic steatosis in patients with a high HBV-DNA level and concluded that there is unlikely an association between HBV infection and hepatic steatosis. In another large scale study in Taiwan by Cheng et al (18) which recruited a total of 33,439 subjects, they showed an inverse relationship between prevalence of fatty liver and positive HBsAg status in subjects older than 50 years and no significant association between HBV infection and fatty liver in subjects younger than 50 years. Although fatty liver was diagnosed via ultrasound and no liver biopsy was performed, the overwhelming statistics on these recent study showed that association between HBV infection and hepatic steatosis is not as strong as what previously thought.…”
Section: Hepatitis B Status and Hepatic Steatosismentioning
confidence: 95%